Analisis Kelayakan Usaha ditinjau dari Aspek Pasar (Studi Kasus pada Usaha Petshop Umara Multi Bisnis) - Ridwan Nashrullah (INDO PUBLISHING, 2026)
This study aims to determine the feasibility of Umara Multi Business Petshop from a market perspective. The type of research used is qualitative research, where data is collected directly in the field through surveys and interviews. The informants in this study consist of three people: the owner of Umara Multi Business Petshop, employees, and consumers. The data analysis used is descriptive analysis of the interview results regarding business feasibility from the market aspect, which includes product, price, place, promotion, people, physical evidence, and process. The results of the study indicate that Umara Multi Business Petshop applies alternative strategies in terms of the market, so it can be said that Umara Multi Business Petshop is feasible for development.